If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(p + 1)(p + 2) = 0 Reorder the terms: 6(1 + p)(p + 2) = 0 Reorder the terms: 6(1 + p)(2 + p) = 0 Multiply (1 + p) * (2 + p) 6(1(2 + p) + p(2 + p)) = 0 6((2 * 1 + p * 1) + p(2 + p)) = 0 6((2 + 1p) + p(2 + p)) = 0 6(2 + 1p + (2 * p + p * p)) = 0 6(2 + 1p + (2p + p2)) = 0 Combine like terms: 1p + 2p = 3p 6(2 + 3p + p2) = 0 (2 * 6 + 3p * 6 + p2 * 6) = 0 (12 + 18p + 6p2) = 0 Solving 12 + 18p + 6p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '6'. 6(2 + 3p + p2) = 0 Factor a trinomial. 6((2 + p)(1 + p)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(2 + p)' equal to zero and attempt to solve: Simplifying 2 + p = 0 Solving 2 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + p = 0 + -2 p = 0 + -2 Combine like terms: 0 + -2 = -2 p = -2 Simplifying p = -2Subproblem 2
Set the factor '(1 + p)' equal to zero and attempt to solve: Simplifying 1 + p = 0 Solving 1 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + p = 0 + -1 Combine like terms: 1 + -1 = 0 0 + p = 0 + -1 p = 0 + -1 Combine like terms: 0 + -1 = -1 p = -1 Simplifying p = -1Solution
p = {-2, -1}
| 13x^2-3x^2=20x+13x | | 5xsquared=100 | | c=ab+d | | X^2-6x+y^2+10y=66 | | 8g+4-5=-5 | | 0=6n^2-43n | | 18x^3-5720=0 | | 4x^2=448 | | x^2-8x-9200=0 | | 4x-3=3(x+1) | | (3a+2)-11b=0 | | 4+3x+1=2x+5+x | | 4x-5=4x+3 | | 3t^2-8t-20=0 | | 23730=x+.13x | | 3x-12x^2=0 | | 21x-6-15x+4=20x-7-14x+4 | | x^2-8x-9400=0 | | y=ln(ln(8x)) | | 9x+1=7x+14 | | 0.02(y-6)+0.12y=0.06y-0.7 | | 7x+x-5=7x+2 | | -18+x=x+144 | | x=7-8y | | 7c-3c+10=2c+20 | | 72x+y=3 | | (8+x)(4x-1)= | | x^2-14x=-81 | | 18x+6y=3 | | sin^2x-1= | | 6x+6=-7+2x+21 | | h(t)=16t^2+140t |